Locomotor activity depends on β-arrestin recruitment by the dopamine D1 receptor in the striatal D1-D3 receptor heteromer - Alexandra H. Evans; Marc Ciruela-Jardí; William Rea; Bradley M. Keegan; Marjorie R. Levinstein; Alessandro Bonifazi; Jianjing Cao; Shelley N. Jackson; Lei Shi; Nil Casajuana-Martin; Ning-Sheng Cai; Vicent Casadó; et al. (Pharmacological Research)
Several dopaminergic compounds, including the clinically used pramipexole, are labelled as preferential dopamine D3 receptor (D3R) agonists based on their moderately higher affinity for the D3R versus other D2-like receptor subtypes. In rodents, these compounds typically produce locomotor depression with low doses and locomotor activation with higher doses, which has been assumed to be mediated by presynaptic D3Rs and postsynaptic striatal D2Rs, respectively. However, studies with selective pharmacological and genetic blockade of each dopamine receptor subtype suggest opposite roles. We address this apparent conundrum by performing a comprehensive in vitro, in vivo and ex vivo pharmacological comparison of several preferential D3R agonists. Their differential properties reveal that their locomotor activating effects in mice are dependent on the striatal postsynaptic D3Rs forming heteromers with D1Rs, via their ability to potentiate β-arrestin recruitment by the D1R in the D1R-D3R heteromer. The results also indicate that the locomotor depressant effects are largely dependent on their ability to activate presynaptic D2Rs. More broadly, it is demonstrated that locomotor activity in mice depends on β-arrestin recruitment by the D1R in the striatal D1R-D3R heteromer. These results can have implications for the treatment of L-dopa-induced dyskinesia and Restless Legs Syndrome.